IMPLEMENTACIÓN DE UN MÓDULO DIDÁCTICO PARA EL ESTUDIO DE ELECTRÓNICA DIGITAL EN EL LABORATORIO DE ELECTRICIDAD Y ELECTRÓNICA, EN LA UNIVERSIDAD TÉCNICA ESTATAL DE QUEVEDO - ANDRADE ESPIMBERA, MIGUEL ANGEL (2025)
The lack of didactic modules in the Electricity and Electronics Laboratory of the Quevedo State Technical University, belonging to the Faculty of Engineering Sciences, is a significant obstacle for academic and practical learning, resorting to the need to use software and electrical simulation programs